Weighing the giants: IV. cosmology and neutrino mass - Mantz, Adam B.; von der Linden, Anja; Allen, Steven W.; Applegate, Douglas E.; Kelly, Patrick L.; Morris, R. Glenn; Rapetti, David A.; Schmidt, Robert W.; Adhikari, Saroj; Allen, Mark T.; Burchat, Patricia R.; Burke, David L.; et al. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We employ robust weak gravitational lensing measurements to improve cosmological constraints from measurements of the galaxy cluster mass function an
in original form 2014 July 16
Gesehen am 05.06.2020